2002
DOI: 10.1046/j.1439-037x.2002.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Auswirkungen eines 10‐jährigen Miscanthusanbaus auf ausgewählte Eigenschaften eines Mineralbodens in Nordostdeutschland

Abstract: Effects of 10 years of Miscanthus cultivation on different properties of mineral soil in North‐east Germany The effects of 4–10 years of Miscanthus cultivation on different soil properties was investigated at Klein Markow (Mecklenburg‐Pommerania, Germany) in variants with and without Miscanthus between 1994 and 2000. Soil containing Miscanthus showed higher concentrations of organic carbon (Corg) (+0,29 %) and total nitrogen (Nt) (+0,03 %) and consequently an increased storage of soil organic matter (SOM) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Estimates of annual soil C sequestration by energy crops such as switchgrass range from 500 to 2900 kg ha -1 (Al-Kaisi et al, 2005;Ma et al, 2000;Sanderson et al, 1999). Kahle et al (2002) observed annual C sequestration of 1220 kg ha -1 in miscanthus plots ranging from 4-to 10-yr old, in northeastern Germany. Our results are at the upper part of the reported ranges.…”
Section: Soil Analysesmentioning
confidence: 99%
“…Estimates of annual soil C sequestration by energy crops such as switchgrass range from 500 to 2900 kg ha -1 (Al-Kaisi et al, 2005;Ma et al, 2000;Sanderson et al, 1999). Kahle et al (2002) observed annual C sequestration of 1220 kg ha -1 in miscanthus plots ranging from 4-to 10-yr old, in northeastern Germany. Our results are at the upper part of the reported ranges.…”
Section: Soil Analysesmentioning
confidence: 99%
“…Rubino et al [36] quantified significant incorporation of 13 C-labelled poplar litter into the topsoil horizon in Italy. Significant input from Miscanthus leaves is unlikely, however [18], despite a potential input of up to 7 Mg C ha −1 year −1 [37][38][39]. Even for late-harvest Miscanthus, leaf fall remains largely undecomposed [22], partly because of its reduced quality arising from the translocation of N from senescing leaves to the rhizome at the end of the growing season [40].…”
Section: Soc and Tn Under Bioenergy Cropsmentioning
confidence: 99%
“…Hence, an appropriate amount of industrial N fertilizer is needed to compensate for the annual soil N losses to maintain the high successive biomass yields of Miscanthus; otherwise, the significant decrease in soil N levels could be caused even over a short establishment period (Placek et al, 2018;Wang et al, 2017). However, many papers suggest that soil N contents are not affected much after Miscanthus establishment (Brami et al, 2020;Duan et al, 2019;Dufossé et al, 2014;Gregory et al, 2018;Kang et al, 2020;Krol et al, 2019;Xu et al, 2021) or even increased (Chen et al, 2009;Das et al, 2016;Dufossé et al, 2014;Kahle et al, 1999Kahle et al, , 2002Nebeská et al, 2018) to some degree in the absence of N supplement independent of the cultivation years and soil types. We previously found that the annual harvest of a large amount of biomass (around 22.22 t/ ha/year) over a long-term period (> 15 years) slightly increased total N (TN) contents of 0-100 cm soil in the absence of N fertilization (Zhao et al, 2020(Zhao et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%